PENGARUH TERAPI MUSIK TERHADAP FUNGSI KOGNITIF PADA LANSIA YANG MENGALAMI DEMENSIA - Aida Yulia; Riana Syafitria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The number of older person with dementia that 220,the found 22 million older person who had dementia and it will be increased in 2030,that 63 million people. Dementia is disease commonly experience of elderly. The main problem that must be appear on the elderly that is a decrease in cognitive function. The intervention to minimizing impaire in cognitive function is music therapy. Music therapy is very effective for increase cognitive function to older person who had dementia at Nursing Home Care Sabai Nan Aluih at Sicincin Padang Pariaman,2017. Design of this study is Quasy Experiment with One Group Prettes-posttest Design, and using Purposive Sampling technique with the number of 10 sample. The time of research do on 5-17 June 2019. The results is show that the score of cognitive function before giving music therapy is 17.1, while the score of cognitive function after giving music therapy is 19.7. Bivariat analysis with use the paired sample t-test, showed that p-value 0,00 (p